Oncologists' Treatment Responses to Mental Health Distress in Their Cancer Patients. (September 2018) - Granek, Leeat; Nakash, Ora; Ben-David, Merav; Shapira, Shahar; Ariad, Samuel
The objectives of this study were to identify how oncologists respond to mental health distress in their patients, what specific strategies they use in treating this distress, and what barriers they report responding to their patients' emotional distress. Twenty-three oncologists at two cancer centers were interviewed. The grounded theory method of data collection and analysis was used. Oncologists varied in their response to patients' emotional distress. Strategies used in responding to patients' distress included creating supportive relationships and prescribing medications, while barriers included patient reluctance, a lack of protocol on how to respond to patients, limited psychosocial resources, and a lack of time. Developing and adopting clear guidelines to addressing mental health distress among cancer patients is critical in assuring quality care for the whole patient and reduce the risk for poor quality of life and potential disease-related morbidity and mortality.